Critical Science and Mathematics Early Childhood Education: Theorizing Reggio, Play, and Critical Pedagogy into an Actionable Cycle - Mandy McCormick Smith; Theodore Chao (MDPI AG, 2018)
Young American children in today's public schools live in a world in which tensions around about identity (i.e., ethnicity and race, gender continuums, language backgrounds and proficiencies, cultural values and beliefs, economic resources, schooled experiences, literacy, and im/migration history) are part of everyday conversation. However, many early childhood science and mathematics educators are reticent to engage deeply in dialogue around these identities, not only due to a common narrative where science and mathematics are interpreted as culturally-neutral, but also because few models within early childhood science and mathematics education exist on how to engage in these conversations. Given this, we ask, how can we prepare and support teachers in developing a positive awareness of culture, identity, diversity, and other critical tensions faced by our youngest learners? How can we prepare and support teachers in engaging in these critical conversations as connected to science and mathematics with young children?